Zanthoxylum rhesta Crude Protein has Promising Pro-apoptotic and Anti-angiogenic Properties - Parrikar, Priyanka Naik; Srinivas, Balaji Kyathegowdanadoddi; Krishnappa, Dharmappa Kattepura; Jayarama, Shankar (Asian Journal of Biological and Life Sciences, 2020)
Zanthoxylum rhesta is a spice tree normally found in the Western Ghats and Asian countries, its fruits are commonly incorporated in regional cuisines as flavoring agents. In this study, the edible nature of this plant has been exploited to establish its pro-apoptotic and anti-angiogenic properties. ZRCP (Zanthoxylum rhesta crude protein) was tested against cell lines of different origins, among these cell lines breast cancer cell line, MCF-7 showed the highest cytotoxicity and was carried for further assays. ZRCP was analyzed for both, in vitro and in vivo effects. This study was supported by assays like MTT assay, apoptotic studies by Giemsa staining, wound healing assay and colony formation assay. The study reflected the pro-apoptotic and anti-angiogenic properties of ZRCP. ZRCP caused apoptosis in MCF-7 cells and also restricted cell growth thus not permitting the cells to proliferate any further. ZRCP also exhibited anti-angiogenic activity in vivo and in vivo. ZRCP exhibited promising activity in vitro and in vivo assays performed, this provided promising facts about the utility of crude protein obtained from Z. rhesta as a pro-apoptotic and anti-angiogenic agent of natural origin.
Keywords: Anti-angiogenic; Anti-cancer; Apoptosis; Crude; MCF-7; Zanthoxylum